Cohesive Markers Used on Thesis Background of English Education Department Students - Wardaningsih, Irda Juni; Rohmana, Rohmana; Sapan, Yulius Tandi (Universitas Halu Oleo, 2021)
This study was conducted to analyse grammatical cohesive markers in students’ thesis background. The objectives of this study was to describe the kinds of grammatical cohesion used in students’ thesis background, to find out the mistake of the use of grammatical cohesion on thesis background, and to know the reason why the students made mistake in their thesis background. The respondents were under graduated students of English Education Department of Halu Oleo University in academic year 2014/2015. The design of this study was qualitative descriptive that consisted of collecting ( reading students’ thesis background), classifying (giving a code in every grammatical item), identifying (determining the incorrect word), analyzing (explaining the mistake and give the correction) and interviewing about the respondents’ mistake. The finding showed that the students were able to apply grammatical cohesion devices in their thesis background which were conjunction, reference, ellipsis and substitution. The students mostly made mistakes in the use of conjunction and reference. The students made mistake because most of them did not give more attention to the background thesis text, they rechecked in such a hurry.